Field Trial Evaluation of the Performances of Point-of-Care Tests for Screening G6PD Deficiency in Cambodia - Roca-Feltrer, Arantxa (PLoS One, 2014)
BACKGROUND: User-friendly, accurate, point-of-care rapid tests to detect glucose-6-phosphate dehydrogenase deficiency (G6PDd) are urgently needed at peripheral level to safely recommend primaquine for malaria elimination. METHODS: The CareStart G6PD RDT (AccessBio, New Jersey, USA), a novel rapid diagnostic test and the most commonly used test, the fluorescent spot test (FST) were assessed against the quantitatively measured G6PD enzyme activity for detecting G6PDd. Subjects were healthy males and non-pregnant females aged 18 years or older residing in six villages in Pailin Province, western Cambodia. FINDINGS: Of the 938 subjects recruited, 74 (7.9%) were severe and moderately severe G6PD deficient (enzyme activity <30%), mostly in male population; population median G6PD activity was 12.0 UI/g Hb. The performances of the CareStart G6PD RDT and the FST, according to different cut-off values used to define G6PDd were very similar. For the detection of severe and moderately severe G6PDd (enzyme activity <30%, <3.6 UI/g Hb) in males and females, sensitivity and negative (normal status) predictive value were 100% for both point-of-care tools. When the G6PDd cut-off value increased (from <40% to <60%), the sensitivity for both PoCs decreased: 93.3% to 71.7% (CareStart G6PD RDT, p = 10(−6)) and 95.5% to 73.2% (FST, p = 10(−6)) while the specificity for both PoCs remained similar: 97.4% to 98.3% (CareStart G6PD RDT, p = 0.23) and 98.7% to 99.6% (FST, p = 0.06). The cut-off values for classifying individuals as normal were 4.0 UI/g Hb and 4.3 UI/g Hb for the CareStart G6PD RDT and the FST, respectively. CONCLUSIONS: The CareStart G6PD RDT reliably detected moderate and severe G6PD deficient individuals (enzyme activity <30%), suggesting that this novel point-of-care is a promising tool for tailoring appropriate primaquine treatment for malaria elimination by excluding individuals with severe G6PDd for primaquine treatment.